Subsurface drip irrigation: status of the technology in 2010 - Lamm, Freddie R.; Bordovsky, J. P.; Schwankl, L. J.; Grabow, G. L.; Enciso-Medina, J.; Peters, R. T.; Colaizzi, P. D.; Trooien, T. P.; Porter, D. O. (My University, 2012)
Subsurface drip irrigation (SDI), although a much smaller fraction of the microirrigated land area than surface drip irrigation, is growing at a much faster rate and is the subject of considerable research and educational efforts in the U.S. This article discusses the growth of SDI, highlights some of the research and extension efforts, and points out some of the challenges to SDI adoption and some of the future opportunities for SDI.
Keywords: Subsurface drip irrigation; Microirrigation; Irrigation design; Irrigation management